2015
DOI: 10.4137/ccrep.s26054
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Magnetic Resonance Imaging Might Complement Two-Dimensional Echocardiography in the Detection of a Reversible Nonischemic Cardiomyopathy

Abstract: We report a case of reversible nonischemic dilated cardiomyopathy in a male in his 60s who presented with an acute heart failure syndrome. Both conventional two-dimensional echocardiography and cardiac magnetic resonance imaging (cMRI) demonstrated severe left ventricular systolic dysfunction; however, both modalities were devoid of significant valvular heart disease as well as the presence of fibrosis, infiltration, inflammation, and scar. After six months of aggressive neurohumoral modulation, there was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Biochemical characterization of small nuclear ribonucleoproteins (snRNPs) showed that most minor spliceosome proteins are shared with the major spliceosome with only seven novel proteins uniquely associated with the minor spliceosome (Schneider et al, 2002;Will et al, 2004). Genetic analysis of human ZRSR2, human FUS, mouse SMN1, and maize RGH3 indicates that these factors predominantly affect U12-type intron splicing even though there is substantial evidence for the proteins to participate in other RNA metabolic processes (Gault et al, 2017;Madanieh et al, 2015;Reber et al, 2016). Here we identify the maize RNA Binding Motif Protein (RBM48) as a minor spliceosome factor which functions to promote cell differentiation and repress cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical characterization of small nuclear ribonucleoproteins (snRNPs) showed that most minor spliceosome proteins are shared with the major spliceosome with only seven novel proteins uniquely associated with the minor spliceosome (Schneider et al, 2002;Will et al, 2004). Genetic analysis of human ZRSR2, human FUS, mouse SMN1, and maize RGH3 indicates that these factors predominantly affect U12-type intron splicing even though there is substantial evidence for the proteins to participate in other RNA metabolic processes (Gault et al, 2017;Madanieh et al, 2015;Reber et al, 2016). Here we identify the maize RNA Binding Motif Protein (RBM48) as a minor spliceosome factor which functions to promote cell differentiation and repress cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical characterization of human small nuclear ribonucleoproteins (snRNPs) showed that most minor spliceosome proteins are shared with the major spliceosome with only seven novel proteins uniquely associated with the minor spliceosome: programmed cell death 7, RNA binding region (RNP1, RRM) containing 3, SNRNP25, SNRNP35, SNRNP48, zinc finger CCCH-type and RNA binding motif containing 1, and zinc finger matrin-type 5 (Schneider et al, 2002;Will et al, 2004). Genetic analysis of human ZRSR2, human FUS RNA binding protein, mouse survival motor neuron 1 (SMN1), and maize RGH3 indicates that these factors predominantly affect U12-type intron splicing even though there is substantial evidence for the proteins to participate in other RNA metabolic processes (Madanieh et al, 2015;Reber et al, 2016;Gault et al, 2017). Here we identify the maize RNA binding motif protein 48 (RBM48) as a minor spliceosome factor, which functions to promote cell differentiation and repress cell proliferation.…”
Section: Introductionmentioning
confidence: 78%